Entrepreneurship Education and Awareness of Entrepreneurial Schemes Among Undergraduate Engineering Final Year Students in Vellore District - Raj, P. Sundar; Yuvapriya, M.; Umamaheswari, K.; Subbalakshmi , A. V. V. S. (International Journal of Accounting and Economics Studies, 2025)
In today’s youth, one can observe the growing, diversified, and innovative skills along with an academic degree by the end of their fourth year of an engineering undergraduate program. Those who are planning to become entrepreneurs, either first or subsequent generation, lack awareness about schemes offered by the government or training offered at educational institutions is insufficient to choose entrepreneurship as a career. To understand the awareness about schemes available in India and training offered at educational institutions as part of career planning, training, and development, a study is conducted on Undergraduate engineering students who are in their final semester. A structured questionnaire is circulated for data collection among engineering institutes’ students of Vellore city of Tamil Nadu state in southern India. Results indicate that awareness about schemes is low, and training offered by the educational institute is insufficient, as they already are aware of the training information through various web sources. Hence, a comprehensive mechanism needs to be framed by the educational institutions to impart entrepreneurship education such that entrepreneurship becomes a career choice of today’s generation, which makes them job creators rather a job seekers.
Keywords: Entrepreneurship Education, Job Creator, Job seeker, Training and Development, Undergraduate Engineering, Higher Educational Institution